Relasi Gender dan Tranformasi Sosial Perspektif al-Qur’an - Kurni, Waesul; Anwar, Hamdani; Febriani, Nur Arfiyah (Al Ashriyyah, 2023)
Gender issues are still considered important issues in the last decade. Issues that arise are issues around gender inequality such as women's inheritance rights, witnesses, guardianship, leadership, social constructs, and so on. Men and women basically have the same pattern of gender relations, namely experiencing dehumanization. Gender injustice in women is considered as the cause of dehumanization, while in men dehumanization is due to their tendency to perpetuate gender oppression. The relationship pattern between the two will never be harmonious and find common ground if the relationship pattern between the two still justifies each other about patriarchal culture. This research is included in the category of literature research, with a qualitative approach. The primary source of the Qur'an will be explained based on the books of tafsir that are referenced in this study. Then it is analyzed descriptively to get a precise picture of the pattern of gender relations in the Qur'an. This article concludes that social transformation in gender relations according to the perspective of the Qur'an consists of four main elements. First, there is a transformation in personal activity, including dress etiquette, food opportunities, a shift from negative stereotypes to respect, and a shift from seductive stereotypes to noble personalities. Second, transformation is taking place in domestic activities, especially in terms of changes in inheritance rights for women. Third, there is a transformation in concern for the environment. Fourth, there are transformations in public activities, such as a shift from patriarchal culture to bilateral culture, recognition of the right to allegiance for women, the right to education, the right to witness, democratic respect for women's opinions, opportunities to achieve achievements in the public sphere, the role of women in medical personnel, and religious tolerance. This article concludes that the Qur'anic perspective provides the foundation for positive social transformation in gender relations.